Implementing Project-Based Learning for Pre-Service English Teachers in Independent Home Teaching Internship - Siti Mariam; Catur Kepirianto; Raharjo Raharjo; Nadiah Ma’mun (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2023)
Due to the Covid-19 pandemic, the Education and Teacher Training Faculty of UIN Walisongo, Semarang, Indonesia offered Independent Home Teaching Internships in the academic year of 2021/2022. The purpose of this research is to explain the implementation of Project-Based Learning by pre-service English teachers, as well as to analyze the problems of teaching EFL learners in Independent Home Teaching Internship. The study employed qualitative descriptive research design. The research participants were 15 pre-service English teachers from the English Education Department. Interviews and documentation were used to collect data. According to the data, Project-based Learning was implemented in this program by creating some learning videos. They were video of learning media and also video of English teaching and learning process. The products of project-based learning must be uploaded in YouTube channel. Because this was the first time a teaching internship completed online via numerous platforms, there were also new concerns and hurdles in completing the program. As part of their online Project-based Learning, students struggled with preparing lesson plans and designing certain learning videos. Practical implications of utilizing this learning model make enhancing students’ critical thinking skills, creativity, motivation and autonomous learners. However, they can solve the several problems namely bad connection of internet access, students’ low motivation in learning English and classroom management in these programs